Out-of-Pocket Expenditures for Delivery for Maternity Waiting Home Users and Non-users in Rural Zambia - Constance P. Fontanet; Jeanette L. Kaiser; Rachel M. Fong; Thandiwe Ngoma; Jody R. Lori; Godfrey Biemba; Michelle Munro-Kramer; Isaac Sakala; Kathleen Lucile McGlasson; Taryn Vian; Davidson H. Hamer; Peter Rockers; et al. (Kerman University of Medical Sciences, 2022)
Background  Utilizing maternity waiting homes (MWHs) is a strategy to improve access to skilled obstetric care in rural Zambia. However, out-of-pocket (OOP) expenses remain a barrier for many women. We assessed deliveryrelated expenditure for women who used MWHs and those who did not who delivered at a rural health facility. Methods  During the endline of an impact evaluation for an MWH intervention, household surveys (n = 826) were conducted with women who delivered a baby in the previous 13 months at a rural health facility and lived >10 km from a health facility in seven districts of rural Zambia. We captured the amount women reported spending on delivery. We compared OOP spending between women who used MWHs and those who did not. Amounts were converted from Zambian kwacha (ZMW) to US dollar (USD). Results  After controlling for confounders, there was no significant difference in delivery-related expenditure between women who used MWHs (US$40.01) and those who did not (US$36.66) (P = .06). Both groups reported baby clothes as the largest expenditure. MWH users reported spending slightly more on accommodation compared to those did not use MWHs, but this difference represents only a fraction of total costs associated with delivery. Conclusion  Findings suggest that for women coming from far away, utilizing MWHs while awaiting delivery is not costlier overall than for women who deliver at a health facility but do not utilize a MWH.